Welfare effects of subsidizing a dead-end network of less polluting vehicles - Antje-Mareike Dietrich; Gernot Sieg (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2011)
This article shows that in the presence of environmental externalities, it may be welfare enhancing to overcome a technological lock-in by a deadend technology through governmental intervention. It is socially desirable to subsidize a dead-end technology if its environmental externality is small relative to the one of the established technology, if the installed base and/or the strength of the network effect is small and if future generations matter. Applying our results to the private transport sector, governments promoting alternatives to gasoline-driven vehicles have to be aware of these opposing welfare effects.
Keywords: O33; L92; Q55; 330; environmental externalities; network effects; private transport; technological change